The impact of key audit matter characteristics on financial statement understandability and investor decision-making: An empirical stud - Nidal Neiroukh; Dilber Caglar (Decision Science Letters)
This study investigates how key audit matter (KAM) characteristics influence financial statement understandability and subsequent investor decision making. Using Structural Equation Modeling-Variance Based (SEM-VB) through Partial Least Squares (PLS), the analysis was conducted on a diverse global sample of investors from Europe, North America, Asia-Pacific, Africa, and Latin America. The results indicate that KAM accuracy, reliability, audit quality, and financial reporting quality significantly enhance perceived financial statement understandability, which in turn positively impacts investor judgments. The mediating role of understandability is confirmed, emphasizing its crucial influence on investors’ decisions. Additionally, an importance-performance map analysis (IPMA) identified KAM reliability and accuracy as the most critical factors. This study contributes to the theoretical and managerial understanding of audit practices and investor behavior.